Wacana Dekolonisasi Ilmu Dan Pembentukan Kearifan Tempatan Melalui Kursus Falsafah Dan Isu Semasa: Discourse on the Decolonization of Knowledge and the Formation of Local Wisdom through Philosophy Courses and Current Issues - Mohd Azhar, Muhammad Hazim (Online Journal of Research in Islamic Studies, 2021)
The Philosophy and Current Issues Course is one of the two courses that have been introduced to students in addition to the Ethics and Civilization course. It is a prerequisite for all students at the undergraduate level to complete the course. It shows the importance of philosophy in our daily life. The initial problem is that philosophy oftenly regarded as difficult, ambiguous, heavenly and has no direction.Such perception need to be changed and philosophy need to be seen as applicable for life. This paper is a result of the discussion of several UiTM lecturers who teach this course. Based on a content analysis approach, this paper aims to build an understanding of the Philosophy Course and Current Issues by discussing on the course information and key topics according to ‘local wisdom’ perspectives to build backgrounds and problems. Indeed this course is critically important due to its noble aims. It is hoped that the course could eventually capable of forming balanced human beings that will produce good society as the cornerstone of a glorious human civilization based on the narrative of local wisdom.